2017
DOI: 10.3390/pathogens6020021
|View full text |Cite
|
Sign up to set email alerts
|

Toxoplasma gondii in the Food Supply

Abstract: Toxoplasmosis is caused by infection with the protozoan parasite Toxoplasma gondii. Infections are usually either asymptomatic or develop mild symptoms that are self-limited, but infections in immunosuppressed persons can be severe. Infections in pregnant women can cause serious health problems in the child such as mental retardation and blindness. Infection with T. gondii in immunocompetent adults can lead to impaired eyesight. Toxoplasmosis has ranked very highly in two studies of death and disability attrib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
25
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(30 citation statements)
references
References 24 publications
4
25
0
1
Order By: Relevance
“…Contrariwise, the only established definitive hosts of N. caninum are dogs, gray wolfs, coyotes, and dingoes that causes a serious disease particularly in ruminants (Belluco et al, 2017;Boas et al, 2015;Donahoe et al, 2015;Dubey, 2003;Hussain et al, 2017;Jones & Dubey, 2012;Klauck et al, 2016;McCann et al, 2008;Oshiro et al, 2015). Recorded data showed that intermediate hosts of T. gondii and N. caninum become infected in two ways of vertical (transplacental) and horizontal (ingestion of oocysts shed in milk and meat) (Belluco et al, 2017;Boas et al, 2015;Donahoe et al, 2015;Dubey, 2003;Hussain et al, 2017;Jones & Dubey, 2012;Klauck et al, 2016;McCann et al, 2008;Oshiro et al, 2015). Thus, contaminated milk and dairy products (particularly traditional dairy products) play an imperative role in the distribution of T. gondii and N. caninum infections to human (Ayinmode, Akinseye, Schares, & Cadmus, 2017;Gos et al, 2017).…”
mentioning
confidence: 99%
“…Contrariwise, the only established definitive hosts of N. caninum are dogs, gray wolfs, coyotes, and dingoes that causes a serious disease particularly in ruminants (Belluco et al, 2017;Boas et al, 2015;Donahoe et al, 2015;Dubey, 2003;Hussain et al, 2017;Jones & Dubey, 2012;Klauck et al, 2016;McCann et al, 2008;Oshiro et al, 2015). Recorded data showed that intermediate hosts of T. gondii and N. caninum become infected in two ways of vertical (transplacental) and horizontal (ingestion of oocysts shed in milk and meat) (Belluco et al, 2017;Boas et al, 2015;Donahoe et al, 2015;Dubey, 2003;Hussain et al, 2017;Jones & Dubey, 2012;Klauck et al, 2016;McCann et al, 2008;Oshiro et al, 2015). Thus, contaminated milk and dairy products (particularly traditional dairy products) play an imperative role in the distribution of T. gondii and N. caninum infections to human (Ayinmode, Akinseye, Schares, & Cadmus, 2017;Gos et al, 2017).…”
mentioning
confidence: 99%
“…30 state the constant risk of human contact with factors causing both diseases. 1,3,4,8,14,18,30,31,38,53 Despite difficulties in diagnosing toxoplasmosis and toxocarosis in humans sanitary services, without keeping records of these diseases and without knowing local threats, cannot take preventive action. 43,58,80-84. Authors of scientific publications advocate conducting a broad education of the population on risks of these diseases.…”
Section: Resultsmentioning
confidence: 99%
“…43,58,80-84. Authors of scientific publications advocate conducting a broad education of the population on risks of these diseases. 4,8,11,19,31,43,48,[85][86][87][88] Failure of such programs cannot be the basis for their abandonment, rather, the cause for their ineffectiveness should be considered,31.89 as it is known that such programs do bring results. 19,88 In Poland, the authorities and state institutions do not provide any such educational programs.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations